Violence In Nursing: Perceived Prevalence and Impact in Community Health Clinics In Cape Town - Adams, Faiza Kajee (Department of Health and Rehabilitation Sciences, 2024)
The paper will be focusing on violence against nurses working in community health clinics in Cape Town. The study is a replication of Prof Doris Deedei Khalil‟s (principle researcher) larger studies on violence in all areas of nursing including general, paediatric and psychiatric nursing, midwifery and undergraduate nursing schools. Aim and objectives: to explore violence in nursing within community health care settings. Some of the objectives of the study examined the extent and frequency of violence against nursing staff in community health clinics. Research design: phenomenological approach was selected to capture experiences and views of nurses working in selected health centres. The sample group or research participants was drawn from seven sub-districts public funded clinics within the Cape Town Metropole Health District, namely Tygerberg, Mitchell‟s Plain and Klipfontein, Southern, Eastern, Western and Northern sub-districts. Categories of nurses that participated in the study were Professional Nurses (RN), Clinical Nurse Practitioners (CNP), Unit Mangers (UM), Registered Auxiliary Nurses, Enrolled Nurses (EN) and Student Nurses. Ethical approval to proceed with data collection and permission to access research sites was granted in 2008. Methods of data collection: data was collected from three sources, i.e. questionnaires, interviews and documents. Although phenomenological approach normally does not use questionnaires as a means of data collection because of the nature of the topic under study, confidentiality has to be assured to avoid the possibility of reprisals or intimidation. Analysis: computer software were utilised to capture information obtained from questionnaires and interviews. Questionnaires and interview responses were compared for similarities and differences. Only official document was made available for the study; therefore triangulation of data sources was possible. Results: The main types of violence were verbal abuse, and threats to assault. Significant number of respondents indicated that women attack nurses more often than gang members and patients‟ relatives. Nevertheless, perpetrators of violence against nurses varied among the sub-districts, e.g. Western sub-district clinics identified women whereas, Klipfontein identified patient relatives and Tygerberg identified gang members as regular perpetrators of violence against staff in their clinics. Results indicated that violent incidences occur on Mondays and Fridays in all the participating clinics. The highest number of violent incidences in Tygerberg clinics occurred on Mondays. On the other hand, threats to assault nurses were high in Western and Southern sub districts clinics compared to the other sub-districts. Conclusions: violence against nurses in 16 most health clinics of the study is on the increase because of substance abuse and gang violence. Recruitment of additional staff could minimise the time patients have to wait to see a doctor. However, it is essential that some nurses working in these clinics be more compassionate and polite towards their patients. Recommendations: increase number of security personnel sub-districts with high frequency of attacks against nurses. Nurses should be encouraged to respect each other and minimise verbal abuses against each other. Nurses that violate patients should be dismissed from the profession